Los inmigrantes en el cine argentino. Panorama general y estudio de un caso actual: Un cuento chino, 2011 - Estela Erausquin (Les Cahiers ALHIM)
This work draws up, in a first part, a panorama (from1933 to our days) of the representation of the immigrants in Argentina's fiction movies. It is possible to observe that there is practically no filmmaking regarding the new Asian immigration, particularly Chinese, in spite of its considerable importance. This is why the movie Un cuento chino (2011) of Sebastián Borensztein arrives just in time.  The study of this film occupies the second part of this article. It is about a fable, a moral tale, whose message points out the importance of the regard of the other, a foreigner, in order to know and love ourselves (and try to love also other people).